A termőföld privatizációjának regionális vetülete - Kovács, Teréz (Tér és Társadalom, 1996)
In Hungary, in the past half a century radical changes took place in land ownership three times. The last one was carried out during the period of the first freely elected government after the change of the political system. In theory, 2 million people, i.e. every fifth citizen acquired some land. For want of skills and capital, many did not use their right and sold their lands as soon as they obtained it. Others lend the gained land. In Hungary there is a very high number of land owners at the moment, but in the land use a concentration can be seen. This led to an equalisation replacing the small homesteads and giant estates typical in the socialist era: There are large, medium size and small estates, as well. The farmers, the co-operatives and the different types of businesses have equal one third shares of the land. The area of lands cultivated by farmers increased by 6-7% from 1994 to 1995. In this period it was mainly the co-operatives that lost some of their lands, which is surprising because the socialist-liberal government, elected in 1994, supported the co-operatives and not the farmers, even if not in a declared way. The proportion of the citizens interested in land privatisation is not even throughout the whole of Hungary. Three regions are spectacular from this aspect: The first one is in the eastern part of Hungary, which is an economically underdeveloped region; The second one is in the western part of the country, where, due to the illegal land purchases of the foreigners, land is a valuable property; The third region is in the south-middle part of Hungary. It is a traditional agricultural region with a high share of vegetable- and fruit growing and viticulture. The counties where land privatisation was less important were mainly the mining counties preferred in the socialist era.